The Myth of Québec Traditional Cuisine at Au Pied de Cochon - Turgeon-Gouin, Catherine (Cuizine)

(untitled) (McGill University Library, 2012)
The Montreal restaurant Au Pied de Cochon, with its ingredient and menu choices, decor, and overall atmosphere, is steeped in Québec tradition. By adding haute cuisine ingredients to traditional recipes, however, Au Pied de Cochon reveals an effort to resuscitate Québec’s cuisine in a specifically gentrified way, or, to use a more contemporary term, in a “bobo” or “bourgeois-bohemian” way. The manner in which Au Pied de Cochon negotiates between tradition and bohemian-bourgeois ideals seems to follow the semiological model of the modern myth developed by Roland Barthes in his 1957 essay “Myth Today.” Using Barthes’ framework of myth, the present study aims to shed light on Au Pied de Cochon’s use of Québec’s traditional cuisine to express “bobo” ideals.